Technology of churned dessert products using puree with fruit and vegetable raw - Yeremchuk, Inna; Pushka, Olga; Bondar, Natalia; Koretska, Iryna; Mykhailova, Nelia (My University, 2014)
Due to the rapid development of tourism in Ukraine a good deal of restaurants, hotel and restaurant complexes, wellness centers increase every year. Therefore, expanding of the range of high nutritional value products applies mostly to restaurant institutions. Sweet dessert product with air structure of sambuc type and using of fruit and vegetable puree from natural raw materials was chosen as an object of the research.
Keywords: легкий десерт; добавки та цукор; отримане яблучне пюре; утворення пухкої маси; пектин; самбук; легкий десерт; добавки и сахар; полученное яблочное пюре; образование пышной массы; sambuc; light dessert; additives and sugar; resulting applesauce; formation of lush weight; pectin; кафедра ділової іноземної мови та міжнародної комунікації; кафедра технології ресторанної і аюрведичної продукції; кафедра іноземних мов професійного спрямування; кафедра готельно-ресторанної справи